The disposition effect among mutual fund participants : a re- examination - Pereira, Paulo (2020)
Using information on mutual fund trades executed from 1998 to 2017 by 31,513 individual investor clients of a major Portuguese financial institution, we study the relationship between the disposition effect, financial literacy and trading experience. We find that mutual fund investors exhibit strong disposition effect. The tendency to hold losers is partially offset with literacy: not only holding a university degree reduces the propensity to hold on to loser funds but also higher financial knowledge and stronger math skills reduce the disposition effect. Literacy also plays a role in shaping the way experience affects this bias. Evidence of the disposition effect persists after accounting for redemption fees, bad emotions, irrational beliefs, market sentiment and the existence of someone to blame.